Research on Vehicle Automatic Driving Target Perception Technology Based on Improved MSRPN Algorithm - Yang, Min (Journal of Computational and Cognitive Engineering, 2022)
Vehicle automatic driving technology can effectively improve the safety performance of vehicle driving. This research is aimed at the needs of vehicle automatic driving. Combined with vehicle perception technology, a better target recognition algorithm is proposed. By comparing the recognition and recall rate of ION algorithm, HYPERNET algorithm, R-CNN (Regions with CNN features) algorithm, and multi-strategy region proposal network (MSRPN) algorithm, it can be seen that MSPRN algorithm has better algorithm performance and is suitable for target detection and recognition in vehicle automatic driving. Received: 5 November 2021 | Revised: 12 December 2021 | Accepted: 10 January 2022 Conflicts of Interest The author declares that he has no conflicts of interest to this work.